Vitamin D Receptor Activation Mitigates the Impact of Uremia on Endothelial Function in the 5/6 Nephrectomized Rats. (14th December 2009) - Wu-Wong, J. Ruth; Noonan, William; Nakane, Masaki; Brooks, Kristin A.; Segreti, Jason A.; Polakowski, James S.; Cox, Bryan
Abstract : Endothelial dysfunction increases cardiovascular disease risk in chronic kidney disease (CKD). This study investigates whether VDR activation affects endothelial function in CKD. The 5/6 nephrectomized (NX) rats with experimental chronic renal insufficiency were treated with or without paricalcitol, a VDR activator. Thoracic aortic rings were precontracted with phenylephrine and then treated with acetylcholine or sodium nitroprusside. Uremia significantly affected aortic relaxation (− 50.0 ± 7.4 % in NX rats versus− 96.2 ± 5.3 % in SHAM at 30 μ M acetylcholine). The endothelial-dependent relaxation was improved to –58.2 ± 6.0 %, –77.5 ± 7.3 %, and –90.5 ± 4.0 % in NX rats treated with paricalcitol at 0.021, 0.042, and 0.083 μ g/kg for two weeks, respectively, while paricalcitol at 0.042 μ g/kg did not affect blood pressure and heart rate. Parathyroid hormone (PTH) suppression alone did not improve endothelial function since cinacalcet suppressed PTH without affecting endothelial-dependent vasorelaxation. N-omega-nitro-L-arginine methyl ester completely abolished the effect of paricalcitol on improving endothelial function. These results demonstrate that VDR activation improves endothelial function in CKD.